R.E.S.P.E.C.T.: Recommendations for Providing Pediatric Palliative Care to Families from Culture-specific Environment (Paliativní medicína, 2025)
The paper presents a set of recommendations for providing culturally sensitive care to families of pediatric patients with palliative care needs. Recommendations were created based on experience and knowledge gained from an international internship and literature data. For clarity, the recommendations were organized into the acronym RESPECT, which itself represents a basic framework and the most important principle of working with families from different cultural backgrounds. The letters of the acronym represent the areas of Reflection, Emotion, Spirituality, Paraphrase, Education, Community and Team, which are further explained in our article.